Determinants of satisfaction for automotive after sales service quality: a preliminary application of AutoSERVPERF Model / Nooraini Mohamad Sheriff, Nur Idayu binti Roslan and Yuhanis binti Yusoff - Mohamad Sheriff, Nooraini; Roslan, Nur Idayu; Yusoff, Yuhanis (Universiti Teknologi MARA, Perlis, 2020)
Successful delivery of customer satisfaction through excellent automotive after sales service quality (AASSQ) can drive long-term profits and reinforces the image of automakers. Customers are generally willing to pay a huge sum of money to secure guarantees and dependable after sales service. Based on this premise, this study determined the automotive after sales service quality dimensions (using AutoSERVPERF model) to deliver customer satisfaction. Data were solicited from 226 respondents who are customers of an automotive after sales service center in Selangor. Convenient sampling technique was used to select volunteer respondents for the survey and a self-administered questionnaire with a 5 point Likert scale was administered for data collection. The responsiveness, empathy, assurance and reliability dimensions of the AutoSERVPERF model were uncovered to be important in delivering satisfaction towards AASSQ. However, among these four dimensions, the empathy and assurance dimensions were perceived to have delivered high performance and are of high importance to customers. Hence, to deliver customer satisfaction towards automotive after sales service, periodic knowledge and skill enhancement training is essential. Instituting clear standard operating procedures, close monitoring and supervision of service staffs would help preserve the consistency and hence reliability of after sales service delivered.